Analysis of Regional Tax Performance in Supporting Post-Covid-19 Fiscal Rehabilitation in Lombok Utara District - Putri Yulia Indrawati; Wahyunadi, Wahyunadi; Eka Agustiani; Tarek Mami (Journal of Social and Humanities, 2024)
This research aims to analyze the Performance of Regional Taxes in Supporting Post-Covid-19 Fiscal Rehabilitation in North Lombok Regency. The data used is secondary data to determine how regional taxes are able to support post-Covid-19 fiscal rehabilitation. The collected data was then analyzed by researchers using Economic Value, Efficiency, Effectiveness and Fiscal Needs analysis tools. The results of the research show that the regional tax performance is classified as economical with a percentage of 87%, and is included in the very efficient category, indicated by a percentage value of 8%. In addition, the regional tax performance of North Lombok Regency is included in the less effective in collecting and administering regional taxes with percentage value 65%. The fiscal needs of North Lombok Regency are 23 times greater than the standard fiscal needs of the entire West Nusa Tenggara province.